The superstar quest: Does youth talent predict professional success for female and male tennis players? (2014)
We estimate the relationship between international youth and professional tennis rankings. We find no difference between the predictiveness of rankings from age 14 & Under versus age 16 & Under competitions. The most persistent predictor of professional success is beating older top ranked juniors. Our results reveal stark gender differences. For example, ordinal junior rankings are more strongly associated with professional success for males than for females. In addition, future tennis stars are better signaled by U14 competition outcomes for females, but by U16 results for males.